A Survey on Software Code Clone Detection to Improve the Maintenance Effort and Maintenance Cost of the Software - Guna, V; Sunil Kumar, M (International Journal of Computer Sciences and Engineering, 2025)
During the development of the software the developers have a chance to copy the code continuously. Due to copying of the code there is a chance of having the identical or more similar code fragments in the software and it is called as software clones or code clones. These clones can be detected from the existing code that is in c, c++, java etc programming languages. By the Argo UML tool to the existing code to generate the class diagrams by using reverse engineering process. In software development process, coping of existing code fragment and pasting them with or without modification is a frequent process. Code clone means copy of an original form or duplicate. Software clone detection is important to reduce the software maintenance cost and to recognize the software system in a better way. There are many software code clone detection techniques such as text- based, token-based, Abstract Syntax tree based etc. and they are used to spot and finding the existence of clones in software system. Mainly detection of clones is on the type-1, type-2 and type-3 clones. These clones can be detected by using several novel algorithms are ARIMA, Back propagation, Multi objective genetic algorithm, support vector machines and also with several hybrid techniques with respect to recall and precision.